Translation, cultural adaptation and psychometric analysis of Urdu version of Victorian; institute of sports assessment – achilles questionnaire for athletes with achilles tendinopathy - Jabbar, Saima; Akram, Sana; Khalid Khan, Abdullah; Arslan, Syed Asadullah; Noreen, Aqsa; Irum, Saiqa (Journal of the Pakistan Medical Association, 2024)
Objective: To translate, culturally adapt and psychometrically analyse the Urdu version of the Victorian Institute of Sport Assessment-Achilles questionnaire. Method: The cross-sectional study was conducted at the Pakistan Sports Board, Lahore, Pakistan, from June 17, 2021, to February 15, 2022, and comprised patients with Achilles tendinopathy in group A and healthy controls in group B. Beaton’s guidelines for cultural adaptation and validation for self-reported measures were followed to translate and validate the Victorian Institute of Sport Assessment-Achilles questionnaire in Urdu language. Data was analysed using SPSS 23. Results: Of the 180 subjects with mean age 28.06±5.95 years, 125(69.6%) were males. There were 130(72.2%) patients in group A and 50(27.8%) controls in group B. The overall mean score of the Victorian Institute of Sport Assessment-Achilles questionnaire was 55.99 + 25.43; group A 41.14±9.54 and group B 94.60±4.22. The Urdu version exhibited excellent internal consistency with Cronbach’s alpha values 0.95, and excellent test-retest reliability (p<0.001). Absolute reliability was expressed by standard error of measurement 5.317 and minimal detectable change 6.38). Convergent validity demonstrated strong correlation with the physical domain (r=0.81) of the Urdu version of the World Health Organisation Quality of Life Brief Version. Conclusion: The Victorian Institute of Sport Assessment-Achilles questionnaire could be utilised for assessing severity of Achilles tendinopathy among Urdu-speaking population for clinical as well as research purposes. Key Words: Achilles tendinopathy, Translation, Psychometrics, Reliability and validity, VISA-A, Pakistan.